2015 IEEE International Conference on Fuzzy Systems (FUZZ-IEEE) 2015
DOI: 10.1109/fuzz-ieee.2015.7337934
|View full text |Cite
|
Sign up to set email alerts
|

Feature and decision level fusion using multiple kernel learning and fuzzy integrals

Abstract: Some chapters of this dissertation contain published material. The following list indicates which publications were used along with notes on author contributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…subject to ||w|| p ≤ 1 and w m ∈ R + , where ||w|| p is the p -norm of w. Though the above expres-sion is notationally for M kernels on the same set of features, it is trivially generalized to multiple features, e.g., different kernels on different subsets of features. 29 Optimization-based MKL solutions, versus fixed rule or heuristic approaches, optimize (using alternating optimization typically) the weights of the kernels and the SVM criteria function. Again, we use p -norm MKL 18,19 to derive the LCS weights.…”
Section: Feature Space Fusion Using P -Norm Mklmentioning
confidence: 99%
“…subject to ||w|| p ≤ 1 and w m ∈ R + , where ||w|| p is the p -norm of w. Though the above expres-sion is notationally for M kernels on the same set of features, it is trivially generalized to multiple features, e.g., different kernels on different subsets of features. 29 Optimization-based MKL solutions, versus fixed rule or heuristic approaches, optimize (using alternating optimization typically) the weights of the kernels and the SVM criteria function. Again, we use p -norm MKL 18,19 to derive the LCS weights.…”
Section: Feature Space Fusion Using P -Norm Mklmentioning
confidence: 99%
“…Another approach to obtain ensemble classification is the use of the Fuzzy Integral (FI) aggregation defined with respect to a Fuzzy Measure (FM) [4][5][6][7][8]. The FI is a non-linear aggregation operator to fuse weighted information from multiple sources, where the weights are captured by a FM.…”
Section: Introductionmentioning
confidence: 99%
“…These works further concluded that DeFIMKL was the best among decision level fusion based FI-FM based ensemble classifiers and thus it has been selected in the work as representative of the FI-FM based ensemble classifier family. However, no in-depth comparison of the FI-FM based ensemble classifier with other ensemble methods have been found in the literature [4][5][6][7][8][9] (discussed in detail in section 2.3). Thus, the motivation of this study is to determine the performance of FM-FI based ensemble methods for the purpose of ensemble classification.…”
Section: Introductionmentioning
confidence: 99%
“…Pinar and colleagues [4][5][6][7][8] built upon the previous works on data-driven FMs and proposed Decision-level Fuzzy Integral Multiple Kernel Learning (De-FIMKL) algorithm as an alternative to algorithmic and algorithm-optimisation hybrid FMs, which aggregates the outputs of SVM classifiers through the use of CFI with respect to a FM learned through a regularised quadratic programming approach. DeFIMKL was compared to FIGA, MKGL and other FI-FM based ensemble classifiers for six datasets.…”
Section: Related Workmentioning
confidence: 99%
“…These ensemble methods have been very popular in the machine learning community due to their ability of producing more accurate results than individual classifiers [2] in a very wide range of application areas [3]. Another approach to obtain ensemble classification is the use of the Fuzzy Integral (FI) aggregation defined with respect to a Fuzzy Measure (FM) [4][5][6][7][8]. The FI is a non-linear aggregation operator to fuse weighted information from multiple sources, where the weights are captured by a FM.…”
Section: Introductionmentioning
confidence: 99%